Successful Aging: Implications for Oral Health - H. Asuman Kiyak, PhD (Blackwell Synergy, 2000)
The past few years have seen a growing emphasis in gerontology on the concept of ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œsuccessfulÃƒÂ¢Ã¢â€šÂ¬Ã‚Â or ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œrobustÃƒÂ¢Ã¢â€šÂ¬Ã‚Â aging. This represents a major paradigm shift in the field from a focus on declines in physical and social functioning, assumptions of the aging process as a downward spiral, and studies on how to manage these declines. Leading the way toward this new perspective on aging, the MacArthur Studies of Successful Aging asked the fundamental question: ÃƒÂ¢Ã¢â€šÂ¬Ã‹Å“What genetic, biomedical, behavioral, and social factors are crucial to maintaining health and functional capacities in the later years?ÃƒÂ¢Ã¢â€šÂ¬Ã‚Â These studies examined longitudinally a large cohort of independent elders on several physical, cognitive, emotional, and social parameters.